Impact of Network Globalization and Manufacturing Network Integration on Global Supply Chain Performance: Mediating Role of Sustainability - Witthaya Mekkham; Chayanan Kerdpitak (International Journal of Supply Chain Management, 2019)
Globalization has diverted the attention of top executive sitting in big buildings towards global supply chains instead of organizational ones. Manufacturing organizations have also developed some systems like Internal Manufacturing Network Integration (IMNI) and network globalization to survive in global supply chains. However, these systems often need sustainability to perform well in global supply chains. This research has aimed to see the role of IMNI and network globalization in Thailand, producing assembled products, which include machinery, transportation equipment, automotive and electronics industrial sectors. The mediating roles of sustainable production and sourcing have also been analyzed in this regard. As far as methodology is concerned, middle and top-level management has been surveyed through questionnaire who belong from such manufacturing organizations of Thailand that are operating globally. SPSS and AMOS were used to analyze the data for reliability, confirmatory factor analysis and structural equation modeling. Results have shown that both IMNI and network globalization have significant impact on global supply chain performance while mediating roles of sustainability sourcing and production were also significant in this regard. Originality of this study is in the fact that supply chain sourcing and production have not been previously used as mediators between network globalization, IMNI and global supply chain performance.